DOES PGE(2) ACT AS A MEDIATOR FOR ENDOTHELIN RELEASE - HAKLAR, GONCAGÜL; YEGEN, ŞEVKET CUMHUR (CHURCHILL LIVINGSTONE, 1994)
To investigate the effect of iloprost (ZK 36374) and thromboxane synthetase inhibitor UK 38485 on endothelin release by the intestinal vascular endothelium after ischemia/reperfusion (IR) injury, five experimental groups were formed. The groups consisted of sham, control, iloprost treated (ILO), UK 38485 treated (TSI), and iloprost + UK 38485 treated (ILO + TSI) groups. The last three groups received the corresponding agents and then the superior mesenteric artery was clamped for 30 min followed by 90 min reperfusion. Endothelin levels in the portal blood and malondialdehyde (MDA), prostaglandin E(2) (PGE(2)) and leukotriene C-4 (LTC(4)) levels in the intestinal tissue were determined. The MDA levels increased significantly in the control group and this increase was reversed in ILO, TSI, and ILO + TSI groups, the two drugs together showing a synergistic effect in preventing lipid peroxidation. The changes in the LTC, levels were not significant among the groups. The increased endothelin levels in the control group were reversed in ILO and TSI groups but these two agents did not have a synergistic effect. Increased PGE, levels were reversed with iloprost but neither UK 38485 nor the combination of the two agents was effective in decreasing PGE, levels. It is concluded that endothelin release after mesenteric IR injury is relatively unrelated to lipid peroxidation and the lipoxygenase pathway. The cyclooxygenase pathway has a direct effect on endothelin release and PGE, may act as a mediator.
Keywords: ISCHEMIA-REPERFUSION INJURY; GUINEA-PIG; PROSTACYCLIN